Epigenetic Mechanism of 5-HT/NE/DA Triple Reuptake Inhibitor on Adult Depression Susceptibility in Early Stress Mice - Meng, Ping; Li, Chunmei; Duan, Sijin; Ji, Shengmin; Xu, Yangyang; Mao, Yutong; Wang, Hongbo; Tian, Jingwei (Frontiers in Pharmacology, 2022)
Major depressive disorder (MDD) is a chronic, remitting and debilitating disease and the etiology of MDD is highly complicated that involves genetic and environmental interactions. Despite the many pharmacotherapeutic options, many patients remain poorly treated and the development of effective treatments remains a high priority in the field. LPM570065 is a potent 5-HT/NE/DA triple reuptake inhibitor and both preclinical and clinical results demonstrate significant efficacy against MDD. This study extends previous findings to examine the effects and underlying mechanisms of LPM570065 on stress vulnerability using a “two-hit” stress mouse model. The “two-hit” stress model used adult mice who experienced early life maternal separation (MS) stress for social defeat stress (SDS) and then they were evaluated in three behavioral assays: sucrose preference test, tail suspension test and forced swimming test. For the mechanistic studies, methylation-specific differentially expressed genes in mouse hippocampal tissue and ventral tegmental area (VTA) were analyzed by whole genome transcriptome analysis in combination with next generation bisulfite sequencing analysis, followed by RT-PCR and pyrophosphate sequencing to confirm gene expression and methylation. LPM570065 significantly reversed depressive-like behaviors in the mice in the sucrose preference test, the tail suspension test and the forced swimming test. Morphologically, LPM570065 increased the density of dendritic spines in hippocampal CA1 neurons. Hypermethylation and downregulation of OXTR in the hippocampal tissues along with increased protein expression of Dnmt1 and Dnmt3a in mice that experienced the “two hit” stress as compared to those that only experienced adulthood social defeat stress, and LPM570065 was able to reverse these changes. Combined, these results suggest that methylation specificity of the gene OXTR in hippocampus may play an important role in early life stress-induced susceptibility to depression and that the5-HT/NE/DA triple reuptake inhibitor LPM570065 may reduce depression susceptibility via the reversal of the methylation of the gene OXTR.